Changes of regional brain activity following Tuina therapy for patients with painful cervical spondylosis: a resting-state fMRI study - Song, Shilong; Fang, Yun; Wan, Xing; Shen, Lili; Hu, Yidan; Lu, Chao; Yue, Tao; Chen, Lu; Chen, Jianhuai; Xue, Mingxin (Frontiers in Neurology, 2024)
Background: The effectiveness of Tuina therapy has been confirmed in treating pain of patients with cervical spondylosis (CS), however, its therapeutic mechanism is still unclear. Methods: A total of 27 patients with CS and 27 healthy subjects (HCs) were enrolled in this study. All patients received Tuina therapy every two days for two weeks. The clinical manifestations of patients were evaluated by the Visual Analogue Scale (VAS) and Neck Disability Index (NDI) before and after treatment. In addition, rs-fMRI data were collected and preprocessed in all patients before and after treatment, as well as HCs. HCs underwent a 1-time rs-fMRI scan, whereas CS patients underwent 2-times of rs-fMRI scan. The measure of regional homogeneity (ReHo) was calculated and compared between groups. Finally, relationships between altered brain regions and clinical characteristics were evaluated by Pearson’s correlation analysis. Results: After Tuina therapy, VAS and NDI scores of patients decreased. Before treatment, CS patients showed higher ReHo values in the left middle temporal gyrus, left thalamus, right anterior and posterior cingulate gyrus, left inferior parietal gyrus and lower ReHo values in the right gyrus rectus when compared with HCs. After treatment, CS patients exhibited higher ReHo values in the left inferior temporal gyrus, right anterior and posterior cingulate gyrus, left inferior parietal gyrus and lower ReHo values in the right rectus gyrus when compared with HCs. CS patients after treatment demonstrated higher ReHo values in the left inferior occipital gyrus when compared with those before treatment. Positive correlations were found between ReHo values of the right rectus gyrus and VAS, NDI scores in CS patients before treatment. Differences of VAS scores between before and after treatment were negatively correlated with ReHo values of the left inferior temporal gyrus in CS patients after treatment. Conclusions: This study demonstrated the presence of asynchronous activity in certain brain regions in CS patients, which might be associated with pain and cervical spine dysfunction. Tuina therapy might modulate asynchronous activity of abnormal brain regions, which might contribute to the effectiveness of Tuina therapy in alleviating pain and cervical spine dysfunction in CS patients.